Abscess and symptoms duration upon presentation should guide decision algorithms for early versus interval appendectomy in children - Faidah Badru; Nicholas Piening; Armando Salim Munoz Abraham; Hector Osei; Jose Greenspon; Kaveer Chatoorgoon; Colleen Fitzpatrick; Gustavo A. Villalona (Elsevier, 2019)
Background: To compare outcomes for complicated appendicitis treated with early versus interval appendectomy and to identify which patients would likely benefit from early appendectomy. Methods: A retrospective review of complicated appendicitis was performed from 2010 to 2015. Patients were divided into early (EA) versus interval appendectomy (IA) groups. We compared demographics, complications and outcomes. Pearson's Chi square analysis and Student's T test analysis were performed. Results: We identified 316 patients (EA group 53% vs. IA group 47%). Interval appendectomy group had longer symptom duration [IA 3.8 vs. EA 2.3 days (p = 0.0001)], increased leukocytosis [IA 18.7 vs. EA 17.2 (p = 0.008)], more initial abscesses [IA 35% vs. EA 13% (p = 0.0001)], more complications [IA 30% vs. EA 19%, (p = 0.013) and prolonged total length of stay [(LOS), p = 0.009]. Subgroup analysis of all patients revealed 80% of patients presented with ≤3 cm abscess and duration of symptoms (DOS) ≤5 days. Interval appendectomy patients with DOS ≤5 days and or ≤3 cm abscess on admission had no differences in clinical presentation. However, these patients had prolonged total LOS (IA 7.7 vs. EA 6.3 days, p = 0.01) and increased complications (IA 29% vs. EA 19%, p = 0.04). Conclusion: The majority of patients with complicated appendicitis in children present with small abscess (≤3 cm) and short symptom duration (≤5 days). This subset of patients might benefit from early appendectomy due to decreased LOS, resource utilization and reduced complications. Key Words: abscess, appendicitis, early, interval